Clinical relevance of RET variants G691S, L769L, S836S and S904S to sporadic medullary thyroid cancer - Machens, Andreas; Frank-Raue, Karin; Lorenz, Kerstin; Rondot, Susanne; Raue, Friedhelm; Dralle, Henning (Clinical endocrinology, 2012)
Background Based on reports of higher frequencies among patients with sporadic medullary thyroid cancer (MTC) relative to external controls, the RET (REarranged during Transfection) variants G691S, L767L, S836S and S904S have been considered disease modifiers, suggesting greater lifetime risks of MTC. Other studies, employing different external controls, failed to confirm this association. Using a complementary approach, this study aimed at exploring differences in clinico-pathological characteristics among patients with sporadic MTC carrying no (wildtype), one (heterozygotes) or both (homozygotes) homologue RET variants in the germline, with wildtype cases acting as internal controls. Methods Included in this investigation were 150 patients with complete genetic information on G691S, L769L, S836S and S904S RET alleles operated on for sporadic MTC at a tertiary referral centre. Results Not one statistically significant dose-response relationship was identified between any RET variant (wildtype vs RET heterozygotes vs homologue RET homozygotes) and patient age at MTC diagnosis, gender, primary tumour size, extrathyroidal extension, numbers of involved and removed lymph nodes, or distant metastasis. L769L and S836S homozygotes, unlike G691S and S904S homozygotes, were either rare or absent, limiting the analyses to comparisons of heterozygosity versus wildtype. On time-to-event analysis, G691S, L769L, S836S or S904S carriers and noncarriers developed MTC at similar rates. Conclusions In carriers and noncarriers of the RET variants G691S, L767L, S836S and S904S, sporadic MTC appeared clinically and pathologically indistinguishable. This observation, along with the inconclusive evidence of previous association studies, calls for larger longitudinal association studies with age- and sex-matched external controls and additional functional studies of RET biology.